2003
DOI: 10.3354/meps247043
|View full text |Cite
|
Sign up to set email alerts
|

Laminaria saccharina photosynthesis measured in situ: photoinhibition and xanthophyll cycle during a tidal cycle

Abstract: Photosynthetic activity in thalli of Laminaria saccharina (Lamouroux) was followed in situ in the upper subtidal zone of a Northern Brittany rocky shore (Roscoff, France), using a submersible pulse amplitude modulated (PAM) fluorometer. Two fluorescence parameters, the effective quantum yield of photosystem II (Φ PSII ) and the relative electron transport rate (rETR), were estimated at various stages of a tidal cycle from 10:00 to 18:30 h, and different light conditions due to variations of water depth and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 32 publications
(40 reference statements)
4
49
1
1
Order By: Relevance
“…Differences in P, PA and PAB sensitivity of the optimum quantum yield in gametes were presumably caused by the degree of damage to PSII components or due to the xanthophyll cycle mediated down regulation of PSII (Gevaert et al 2003). The interactive effects of radiation and exposure time treatments, however, showed that the measurable effects of different doses of PAR and UVR in the reduction of photosynthetic efficiency can be similar but the mechanisms behind PAR-and UVR-induced inhibition of photosynthesis are different (Franklin et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in P, PA and PAB sensitivity of the optimum quantum yield in gametes were presumably caused by the degree of damage to PSII components or due to the xanthophyll cycle mediated down regulation of PSII (Gevaert et al 2003). The interactive effects of radiation and exposure time treatments, however, showed that the measurable effects of different doses of PAR and UVR in the reduction of photosynthetic efficiency can be similar but the mechanisms behind PAR-and UVR-induced inhibition of photosynthesis are different (Franklin et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Intertidal algal growth, development, reproduction and productivity are drastically affected by changes in temperature, humidity, salinity, irradiance (both photosynthetically active radiation [PAR] and ultraviolet radiation [UVR]) and nutrient availability (Dring 1982, Lobban & Harrinson 1994, Davison & Pearson 1996, Häder & Figueroa 1997, Gévaert et al 2003, Gao & Xu 2010, Karleskint et al 2010. The expected increase in atmospheric CO 2 and the concomitant ocean acidification due to global climate change might increase or negate the effect of these stressors, and the response and strategies of adaptation and acclimation to these stressors must be studied according to realistic global change scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…and L. digitata. The response of Φ PSII to high irradiances was associated to an increase in the nonphotochemical quenching and was explained as a down-regulation of the photosystem II (Gévaert et al, 2003;Delebecq et al, 2011).…”
Section: Variation In the Trends Of Photosynthetic Performance Accordmentioning
confidence: 99%